Avaliação da funcionalidade em crianças com mielomeningocele - Façanha, Dilene Maria de Araújo (2015)
The Spina Bifida is a type of spine’s congenital ma lformation and spinal cord, caused by several factors. It causes limitations to the child ren’s development and their functionality, requiring assistance, multidisciplinary monitoring and interdisciplinary rehabilitation interventions. Nursing operates in this process and thus on the above, we sought to avaliate the children's functionality with Spina Bifida and verify if the families have offered the care according to their needs. It was made a descriptive transversal study with a quantitative approach. It was applied a structured questionnaire documenting the functional abilities of the child, the caregivers’ assistance and environmental changes in self-care areas, mobility and social function. The study included 79 (seventy-nin e) children, aged from 3 to 7,5 years, diagnosed with Spina Bifida. The research was leade d at Neurorehabilitation Center SARAH, in Fortaleza. In the results obtained were observed that in the functional skills, children had lower development than expected. Promoting the chil dren’s independence in their own residences, by provisioning favorable conditions fo r them, or improving their skills giving them less assistance, could lead them to a greater mobility, improving self-care. In assistance was observed bigger reliance on the mobility area, linked to transfers’ problems, locomotion in the external environment and stairs. In self-car e area was provided more assistance in the care of the bladder and the neurogenic bowel, in th e bath, toilet training and lower limbs’ clothing. In Social function, the difficulties were in solving problems, safety and functional expression, being the area with less assistance fro m caregivers and increased independence of children. Children have shown to be functional in s elf-care for feeding, oral hygiene, hair care, nose and face and upper limbs’ clothing. In m obility, children increased independence on the transfer and mobility in bed, indoors, dragg ing or using supported gait. The obvious changes happened in childhood and during the rehabi litation process. Therefore, it is concluded that children with Myelomeningocele have a lower performance in functional abilities, but could be stimulated to develop their potential in rehabilitation process. The caregiver provides care, even in areas where childr en show independence, but is necessary to reduce the over-protection and encourage the stimul ation of these children by caregivers. Therefore, health promotion is favored with life qu ality to the mother/child pair, increasing social inclusion and autonomy to that public during adolescence. Rehabilitation nursing has a fundamental role with the team, focusing on self-ca re training or caregiver assistance guidance with knowledge, humanism and quality. It i s believed that to evaluate the children’s functionality through quantifiable tool is somethin g of great value to neurology’s professionals, because it’s guide this public and t he caregivers profile, envisioning what could be enhanced and promoted for their independence